Price elasticity of demand for cigarettes in Nepal: Evidence from a lower middle-income country in South Asia using Deaton’s demand model - Vishnu Prasad Sapkota; Umesh Prasad Bhusal; Nirmal Kumar Raut (PLoS ONE, 2026)
Background In South Asia, taxation policies are popular instruments to reduce high cigarette demand which work through directly affecting cigarette prices. The effectiveness of such policies depends on consumers’ behavioural responses to changes in cigarette price, which is commonly expressed in terms of the price elasticity of demand. A limited number of studies in this region have used available cross-sectional and panel survey data to estimate cigarette price elasticity using Deaton’s demand model, and to date, no such study exists for Nepal. Therefore, this study aims to estimate the price elasticity of cigarette demand in Nepal. Methods We applied Deaton’s demand model to estimate cigarette price elasticity utilizing data from the Nepal Household Risk and Vulnerability Survey, a three-year panel microdata (2016–2018). The analysis is based on data from 5,653 households observed over three waves. Deaton’s demand model exploits spatial variation in unit values of cigarettes to measure price elasticity. We adjusted the basic model for possible bias that may arise from panel nature of the data. Results In this study, we found the estimate of price elasticity for cigarettes to be −0.58 [95% CI: −0.79, −0.37]. This indicates that the demand for cigarettes is relatively inelastic. Similarly, we found the estimate of expenditure elasticity to be 1.06 [95% CI: 0.54, 1.57], indicating a more responsive cigarette demand with respect to income. Conclusion The negative price elasticity estimate indicates that the increase in excise taxes can be effective both in reducing cigarette consumption and raising tax revenues. This also provides additional evidence that routine surveys can be valuable for estimating price elasticity using Deaton’s method, which are originally designed to monitor living standards.